1998
DOI: 10.1007/s004220050467
|View full text |Cite
|
Sign up to set email alerts
|

Spatial asymmetries in cat retinal ganglion cell responses

Abstract: Enroth-Cugell and Robson (1966) first proposed a classification of retinal ganglion cells into X cells, which exhibit approximate linear spatial summation and largely sustained responses, and Y cells, which exhibit nonlinearities and transient responses. Gaudiano (1992a, 1992b, 1994) has suggested that the dominant characteristics of both X and Y cells can be simulated with a single model simply by changing receptive field profiles to match those of the anatomical counterparts of X and Y cells. He also propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…For ganglion cells, this is illustrated in Figure 11. Gaudiano (1992aGaudiano ( ,b, 1994 and Gaudiano et al (1998) already suggested that receptive field size could play a role in the generation of retinal nonlinearities. Our results support this view, but the push-pull intraretinal connectivity he introduced does not seem to be necessary for nonlinear responses.…”
Section: Nonlinearities In Retinal Neuronal Responsesmentioning
confidence: 99%
“…For ganglion cells, this is illustrated in Figure 11. Gaudiano (1992aGaudiano ( ,b, 1994 and Gaudiano et al (1998) already suggested that receptive field size could play a role in the generation of retinal nonlinearities. Our results support this view, but the push-pull intraretinal connectivity he introduced does not seem to be necessary for nonlinear responses.…”
Section: Nonlinearities In Retinal Neuronal Responsesmentioning
confidence: 99%
“…Over the last four decades, several computational models have been proposed to explain the function of the retina as a whole, or of particular cell classes, in a variety of species (e.g., Rodieck 1965;Rodieck and Stone 1965a,b;Enroth-Cugell and Shapley 1973;Richter and Ullman 1982;Dawis et al 1984;Kruk and Wrobel 1986;Enroth-Cugell and Freeman 1987;Victor 1987a,b;Maguire et al 1989a;Ö g˘men and Gagne´1990b;Werblin 1991;Gaudiano 1992aGaudiano ,b,1994Maguire 1995;Shah and Levin 1996a,b;Gaudiano et al 1998;Awatramani et al 1997;Berry et al 1999;Wu et al 2000;Kamermans et al 2001). One emerging computational principle is that light adaptation is carried out by two complementary mechanisms: one is the control of transduction/transmission gain over time (temporal adaptation) (e.g., Grabowski et al 1972;Boynton and Whitten 1970;Dowling and Ripps 1972;Baylor et al 1974a,b;Carpenter and Grossberg 1981), and the second is the control of the activity distribution over the retinal network via spatial interactions among retinotopically neighboring cells (spatial adaptation) (Rodieck 1965;Rodieck and Stone 1965a,b;Richter and Ullman 1982;Fleet et al 1985;Enroth-Cugell and Freeman 1987;Ö g˘men and Gagne1 990b;Smirnakis et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The push-pull mechanism in Y-cells is far away from equilibrium and therefore signal summation is strongly nonlinear with different. dynamics than X-c:ells [3,4]. In LGN the different.…”
Section: Introductionmentioning
confidence: 99%